Case Report: Healing a Traumatic Birth - Klaus, Phyllis (Frontiers in Psychology, 2020)
One needs to recognize that the perinatal period is a vulnerable time where negative attitudes, words and actions can have an emotionally damaging effect. Birthing women are especially sensitive to how they are treated. This case report depicts a traumatic birth in which the mother was needlessly separated from her baby. The effect on the birthing mother and her baby from the insensitivity of the personnel had an emotionally devastating impact on the mother/baby relationship that could have been avoided. This report will demonstrate psycho therapeutic methods to heal this distress.